2007
DOI: 10.1111/j.1348-0421.2007.tb04009.x
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Blood Test for Transmissible Spongiform Encephalopathies by Detecting Carbohydrate‐Dependent Aggregates of PrPres‐Like Proteins in Scrapie‐Infected Hamster Plasma

Abstract: PrPres has rarely been detected in blood (except in leukocytes) even in diseased animal models that are known to contain a large amount of PrPres in infected tissues. It seems likely that PrPres detection in blood is difficult because of the low titer of infectious material within the blood. Here, we demonstrate the detection of proteinase K‐resistant 3F4‐reactive protein in the plasma of scrapie‐infected hamsters but not in the plasma of mock‐infected hamsters by partial purification using a novel method term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…26 As we experienced in our experiments, dilution of the scBrh with TBS-SDS resulted in almost diminished on the 30 kDa band and the smaller recovery of the PrPsc than expected even used the same volumes of original one. So, if we compared the observed patterns of PrPsc in standard lane of PK-scBrh on Figure 1 to that on Figures 2-5 electrophoresis patterns were quite different each other especially on their Mw and the intensity of the PrPsc signals on Figures 2-5 were unexpectedly low.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…26 As we experienced in our experiments, dilution of the scBrh with TBS-SDS resulted in almost diminished on the 30 kDa band and the smaller recovery of the PrPsc than expected even used the same volumes of original one. So, if we compared the observed patterns of PrPsc in standard lane of PK-scBrh on Figure 1 to that on Figures 2-5 electrophoresis patterns were quite different each other especially on their Mw and the intensity of the PrPsc signals on Figures 2-5 were unexpectedly low.…”
Section: Discussionmentioning
confidence: 75%
“…We previously reported that mixing of scBrh with mcPl resulted in the appearance of novel antiPrP mAb-reactive protein bands, in a manner similar to the scPl-derived bands yielded by ASP. 26 This observation suggested that the PrPres may be associated with additional partner substances in the blood of infected animals and hence can be precipitated. However, the substances that may become associated with the PrPres in the blood of infected animals have not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acidic SDS precipitation method was H. Abdel-Haq proposed by Tsukui et al (2007) and is based on the detection of carbohydrate-dependent aggregates of PrPreslike proteins in the plasma of scrapie-infected hamsters. The immunocapillary electrophoresis technique consists of fluorescence-based detection of PrP TSE in a competitive immunoassay in which a fluorescently labelled synthetic prion peptide and a polyclonal antibody against this peptide are titrated (Lourenco et al, 2006).…”
Section: Other Approachesmentioning
confidence: 99%
“…Platelets from scrapie-infected hamsters were not able to transmit scrapie; 31 however, PrP Sc in plateletfree hamster plasma samples were detected by PMCA. 32,33 Other studies also revealed that PrP Sc infectivity exists in the cell-free plasma of sheep. 34,35 These findings suggest the presence of varying infectivity in rodents and ruminants.…”
mentioning
confidence: 99%